2005
DOI: 10.1080/14733140512331343840
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of inadequacy, insecurity, and incompetence among experienced therapists

Abstract: Feelings of incompetence are an ongoing part of the private experience of being a therapist. They are often linked to therapist stress, distress, and to negative therapeutic processes and outcomes, yet systematic inquiries into the subjective judgment of experienced therapists as inadequate and incompetent in their professional roles are rare. A qualitative approach was used in this study to obtain rich descriptions of encounters with feelings of incompetence among experienced therapists. Eight therapists with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 14 publications
1
31
0
4
Order By: Relevance
“…A trainee's transition among the various developmental stages is seldom smooth (Skovholt & Rivers, 2004) and the ambivalence or uncertainty inherent in this process might have interfered with the trainee's realistic assessment of his or her abilities. However, a more likely explanation is that these trainees were encountering unique personal distress, or preoccupation with effectiveness that was not being addressed in their training or supervision (Skovholt & Ronnestad, 2003;Thériault & Gazzola, 2005).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A trainee's transition among the various developmental stages is seldom smooth (Skovholt & Rivers, 2004) and the ambivalence or uncertainty inherent in this process might have interfered with the trainee's realistic assessment of his or her abilities. However, a more likely explanation is that these trainees were encountering unique personal distress, or preoccupation with effectiveness that was not being addressed in their training or supervision (Skovholt & Ronnestad, 2003;Thériault & Gazzola, 2005).…”
Section: Resultsmentioning
confidence: 95%
“…Since self-efficacy is a well-established mediator of performance, it can serve as a desirable intermediate outcome of graduate-level education. It is clear that beginning practitioners require a greater amount of instruction, support, and guidance very early on in the training process because they experience anxiety and other debilitating emotions that erode their felt sense of confidence (Heppner & Roehlke, 1984;Thériault & Gazzola, 2005). An efficacy-based individualized plan where trainees are encouraged to engage in a constant comparison between perceptions of efficacy and actual evidence of competence (e.g., from video-taped sessions) would begin to address some of these constraints.…”
Section: Implications For Training Supervision and Practicementioning
confidence: 99%
“…The notion of personal growth during formal training is often left unexplored in the empirical literature, despite the fact that research on experienced therapists has revealed that personal qualities are more crucial to the therapeutic process than treatment techniques (Theriault & Gazzola, 2005). Although schools of experiential psychotherapy emphasize this type of self-development, little empirical evidence has actually even documented it.…”
Section: Discussionmentioning
confidence: 98%
“…Beyond these self-doubts, a trainee's negative affect can adversely influence the client and session (Melton, Nofzinger-Collins, Wynne, et al, 2005), although this phenomenon is not unique to trainees. Theriault and Gazzola (2005) found that even experienced therapists often have ongoing feelings of inadequacy, insecurity, and incompetency, which are also correlated with a host of negative therapy processes/outcomes.…”
Section: Identifying Challenges In Trainingmentioning
confidence: 98%
“…There is evidence that being a therapist can have a negative impact, including depletion of emotional reserves; reduced empathy for family members; feelings of inadequacy and incompetence; adverse effects on friendships; decreased levels of socialisation; and a lessened ability to be genuine, spontaneous and comfortable (Guy, Poelstra, & Stark, 1988;Kottler, 1986;Theriault & Gazzola, 2005).…”
Section: Introductionmentioning
confidence: 98%